Prevalence and Spectrum of Coronary Anomalies Detected on Coronary Computed Tomography Angiography: A single centre experience in Oman - Al-Umairi, Rashid S. (Sultan Qaboos Univ Med J, 2019)
OBJECTIVES: Coronary artery anomalies (CAAs) are uncommon congenital abnormalities with a prevalence ranging from 0.2–2%. CAAs can be asymptomatic or less commonly present with life-threatening symptoms. This study aimed to investigate the prevalence and spectrum of CAAs in patients who underwent coronary computed tomography angiography (CCTA) in Oman. METHODS: This retrospective study was conducted at the National Heart Centre, Muscat, Oman between September 2012 and August 2018. All consecutive patients who had undergone CCTA were included. RESULTS: A total of 4,445 patients were included in this study. Of these, 59 patients (1.3%) were diagnosed with CAAs with a mean age of 52.6 years (range: 12–80 years) and an equal gender distribution. Among the patients with CAAs, the majority (69.5%) had anomalous origins from the opposite or non-coronary sinus. Right coronary artery arising from the left coronary sinus was the most common type (33.9%). Fewer patients (18.6%) had left circumflex arising from the right coronary sinus (RCS). Seven patients (11.9%) had left main arising from the RCS. Other CAAs were in the dual left anterior descending artery (8.5%), high coronary artery take-off (6.8%), single coronary ostia (6.8%) and coronary artery fistula (6.8%). CONCLUSION: The prevalence of CAAs was 1.3% which is similar to the literature.